2018
DOI: 10.18052/www.scipress.com/sfp.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation of a Mixture of Saponin-Rich Plants to Reduce Ammonia-Nitrogen Excretion in Juvenile Nile Tilapia (<i>Oreochromis</i> <i>niloticus</i>)

Abstract: The intensification in aquaculture production leads to increasing attention on the management of ammonia from its waste. Natural solutions such as Yucca schidigera extracts have shown beneficial effects. Their origin (harvested from the wild), however, call for alternative and equally efficient solutions in order to increase the sustainability of their production. In this work, juvenile Nile tilapias (Oreochromis niloticus) were supplemented with different doses of a commercial mixture of saponin-rich plants (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Güroy et al (2016) reported a positive impact of supplementation of juvenile striped catfish (Pangasus hypophthalmus) with a combination of Y. schidigera and QS on the fish total ammonia nitrogen reduction. Saponins' capacity to bind ammonia and promote ammonia transfer to nitrite and nitrate may be a potential explanation to understand the reduced total ammonia nitrogen and unionized ammonia; the latter is the much more toxic form of nitrogen (Engler et al, 2018). Furthermore, saponins' increased intestinal permeability leads to higher absorption of feed nutrients that could better control ammonia nitrogen's overall excretion (Francis et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Güroy et al (2016) reported a positive impact of supplementation of juvenile striped catfish (Pangasus hypophthalmus) with a combination of Y. schidigera and QS on the fish total ammonia nitrogen reduction. Saponins' capacity to bind ammonia and promote ammonia transfer to nitrite and nitrate may be a potential explanation to understand the reduced total ammonia nitrogen and unionized ammonia; the latter is the much more toxic form of nitrogen (Engler et al, 2018). Furthermore, saponins' increased intestinal permeability leads to higher absorption of feed nutrients that could better control ammonia nitrogen's overall excretion (Francis et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, many studies have focused on the role of YS in mitigating ammonia in aquaculture water with promising findings (Castillo Vargasmachuca et al, 2015;Hassan et al, 2017;Yang et al, 2015;Yu et al, 2015). In this regard, YS inclusion can lower TAN and UIA in the carp fish (Dawood et al, 2021;Wang et al, 2020), Nile tilapia (Abdel-Tawwab et al, 2021;Engler et al, 2018), catfish (Güroy et al, 2014;Kelly & Kohler, 2003) and Pacific white shrimp (Litopenaeus vannamei) and Kuruma shrimp (Marsupenaeus japonicus) (Santacruz-…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal histomorphology of fish exposed to different experimental treatments for 60 day addition, the increase in intestinal permeabilization by saponins leads to a better nitrogen absorption that could better manage the total ammonia nitrogen excretion (Engler et al, 2018).…”
Section: Ta B L Ementioning
confidence: 99%
“…More specifically, the intensive conditions produce abundant amounts of ammonia emissions, which induces oxidative stress, immunosuppression, and inflammatory features in a fish’s body [ 42 ]. The inclusion of yucca extract improved the quality of rearing water and lowered the accumulated ammonia in the case of mirror carp [ 42 ], Nile tilapia ( O. niloticus ) [ 12 , 17 ], striped catfish ( P. hypophthalmus ) [ 52 ], and European seabass juveniles ( D. labrax ) [ 45 ]. Yucca extract has steroidal saponins and glycol with an active surface attributed to ammonia’s adsorption [ 34 ].…”
Section: Yucca As a Natural Cleaner For Aquatic Water Qualitymentioning
confidence: 99%
“…Yucca plant originates from the deserts of the Southwestern United States and Mexico, which is known for their high temperature, lack of water, and stressful conditions [ 10 ]. Concurrently, yucca is characterized by its anti-stressor potential and beneficial effects that make it a prospective phytogenic additive for the aquaculture industry [ 12 , 17 ]. Yucca has abundant amounts of saponin and resveratrol, which can eliminate the waterborne ammonia and lower its impacts on aquatic animals’ performance and health [ 18 ].…”
Section: Introductionmentioning
confidence: 99%